2009
DOI: 10.1176/appi.neuropsych.21.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG Abnormalities are Associated With Memory Impairment in Recently Abstinent Methamphetamine-Dependent Individuals

Abstract: This study examined the association between brain electrical activity, measured using quantitative electroencephalography (QEEG), and performance on measures of episodic memory in a sample of nine methamphetamine-dependent individuals who were evaluated after 4 days of monitored abstinence and 10 non-drug-using comparison subjects. In methamphetamine users, but not in comparison subjects, increased theta power was correlated with poorer performance on the delayed recall subtests of the Rey Auditory Verbal Lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
1
9
0
2
Order By: Relevance
“…The demographic summary of the METH‐dependent individuals in this study is different than what is typically reported in studies of METH‐associated cognitive dysfunction, and may contribute to the differences found. For example, the average age (31.3 years) of our participants is similar to other reports (range 27.5–39.38 years) 36–41 . However, the mean number of years of education completed (11.14) is lower than what has been reported elsewhere (11.7–13.9 years) 36–40,42–49 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The demographic summary of the METH‐dependent individuals in this study is different than what is typically reported in studies of METH‐associated cognitive dysfunction, and may contribute to the differences found. For example, the average age (31.3 years) of our participants is similar to other reports (range 27.5–39.38 years) 36–41 . However, the mean number of years of education completed (11.14) is lower than what has been reported elsewhere (11.7–13.9 years) 36–40,42–49 .…”
Section: Discussionsupporting
confidence: 85%
“…However, the mean number of years of education completed (11.14) is lower than what has been reported elsewhere (11.7–13.9 years) 36–40,42–49 . In addition, although epidemiological reports indicate that at least half of METH users are female, studies examining the effects of METH on cognition typically include a lower percentage of females (23–46%) 38–42 , 50,51 . Even in studies where the gender distribution is more equitable, sex differences are rarely examined 45,47,48,52 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Methamphetamine (METH) abuse is a significant public health problem with annual prevalence rate of abuse in 2013 in >1% of adolescents and young adults ( Johnston et al, 2014 ). Extensive clinical evidence indicates that METH abuse causes significant neurocognitive deficits ( Kalechstein et al, 2003 , 2009 ; Gonzalez et al, 2004 ; Hoffman et al, 2006 ; Cherner et al, 2010 ; Casaletto et al, 2014 ). For example, episodic memory is reduced among participants with a history of METH abuse (approximately 11 years), as assessed by performance in learning and recall tests ( Casaletto et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased theta quantitative EEG power was correlated with decreased reaction times in complex tasks and diminished accuracy on the N-back working memory task [8]. Others have shown that increased theta power (slow wave) in abstinent MA users is correlated with deficits in performance on verbal and nonverbal learning and memory tests [9] and other symptoms (hypertension, elevated heart and respiratory rates, hallucinations) [1, 10]. While MA-induced seizures are typically transient, there are cases showing status epilepticus [1].…”
Section: Introductionmentioning
confidence: 99%